L-carnitine: new perspectives on the management of preterm infants - Sisi, Mo; Yong, Lin; Lixing, Qiao; Changsheng, Guo; Jin, Yao; Hang, Zhou; Xing, Cao; Heng, Liu (Frontiers in Nutrition, 2025)
L-carnitine, a quaternary ammonium compound derived from amino acids, serves an essential role in fatty acid metabolism. The functions of L-carnitine include assisting long-chain fatty acyl-CoA across the mitochondrial membrane to promote mitochondrial β-oxidation, reducing oxidative stress damage, and maintaining cellular energy homeostasis. Therefore, postnatal L-carnitine deficiency may lead to impaired fatty acid oxidation, resulting in clinical manifestations of hypoglycemia, hypothermia, acidosis and infection. However, there is still no clear consensus on the need for prophylactic use of L-carnitine in the treatment of preterm infants. This review synthesizes the theoretical foundations and clinical evidence for L-carnitine in preterm infant management, revealing that L-carnitine exerts demonstrable effects on promoting neurodevelopment and preventing neonatal complications. Furthermore, it explores the potential value and current controversies surrounding its prophylactic application.